2016
DOI: 10.1186/s13104-016-2132-1
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly in a patient with a pulmonary neuroendocrine tumor: case report and review of current literature

Abstract: BackgroundPulmonary neuroendocrine tumors (NET) form a heterogeneous group of rare diseases. In these tumors, paraneoplastic syndromes have been described to drive the course of the disease, among them acromegaly induced by paraneoplastic secretion of growth hormone-releasing hormone (GHRH).Case presentationWe report the case of a 43 years old patient initially diagnosed with acromegaly accompanied by weight gain and acral enlargement. Subsequently, further diagnostic work-up identified a solitary pulmonary ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Ectopic secretion of GH from extra-pituitary tumors, causing less than 1% of acromegaly cases, was documented in case reports describing patients with bronchial or pancreatic neuroendocrine tumors and lymphomas [70,71,72,73]. There are also reports of ectopic acromegaly due to a GH-secreting pituitary tumor in the sphenoid sinus [74,75].…”
Section: Extra-pituitary Tumorsmentioning
confidence: 99%
“…Ectopic secretion of GH from extra-pituitary tumors, causing less than 1% of acromegaly cases, was documented in case reports describing patients with bronchial or pancreatic neuroendocrine tumors and lymphomas [70,71,72,73]. There are also reports of ectopic acromegaly due to a GH-secreting pituitary tumor in the sphenoid sinus [74,75].…”
Section: Extra-pituitary Tumorsmentioning
confidence: 99%
“…On the other hand, paraneoplastic acromegaly was described in pulmonary neuroendocrine tumors [ 15 ]. Laboratory tests revealed markedly increased growth hormone (GH) and insulin-like growth factor 1 (IGF-1) without GHRH elevation.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate was 53% and the median PFS was 11.1 months. 50 Another recent study published in 2021 included 31 patients with a fairly equal number of AC (17) and TC ( 14) tumors. This study demonstrated SD in 77.4% of patients with a median PFS of 28.6 months.…”
Section: A) Somatostatin Analog Therapymentioning
confidence: 99%
“…Abbreviations: BPNET, Bronchopulmonary Neuroendocrine Tumor and insulin-growth factor 2. 17,18 There is limited utility of routine baseline plasma chromogranin A (CgA) testing in patients with BPNETs and poor correlation with disease status. 19 CgA can also be falsely elevated with renal impairment, atrophic gastritis, and the use of proton pump inhibitors.…”
Section: Introductionmentioning
confidence: 99%